A world at war, 1911-1949
1 online resource.
Keywords: In A World At War, 1911-1949 , leading and emerging scholars of the cultural history of the two world wars begin to break down the traditional barriers between the historiographies of the two conflicts, identifying commonalities as well as casting new light on each as part of a broader mission, in honour of Professor John Horne, to expand the boundaries of academic exploration of warfare in the 20th century. Utilizing techniques and approaches developed by cultural historians of the First World War, this volume showcases and explores four crucial themes relating to the socio-cultural attributes and representation of war that cut across both the First and Second World Wars: cultural mobilization, the nature and depiction of combat, the experience of civilians under fire, and the different meanings of victory and defeat. Contributors are: Annette Becker, Robert Dale, Alex Dowdall, Robert Gerwarth, John Horne, Tomás Irish, Heather Jones, Alan Kramer, Edward Madigan, Anthony McElligott, Michael S. Neiberg, John Paul Newman, Catriona Pennell, Filipe Ribeiro de Meneses, Daniel Todman, and Jay Winter.